1999
DOI: 10.1128/mcb.19.4.2967
|View full text |Cite
|
Sign up to set email alerts
|

An Activator Binding Module of Yeast RNA Polymerase II Holoenzyme

Abstract: The Mediator complex of Saccharomyces cerevisiae is required for both general and regulated transcription of RNA polymerase II (PolII) and is composed of two stable subcomplexes (Srb4 and Rgr1 subcomplexes). To decipher the function of each Mediator subcomplex and to delineate the functional relationship between the subcomplexes, we characterized the compositions and biochemical activities of PolII-Mediator complexes (holoenzymes) prepared from several Mediator mutant strains of S. cerevisiae. We found that ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
166
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(183 citation statements)
references
References 50 publications
(61 reference statements)
16
166
1
Order By: Relevance
“…Mutations in the tail module components sin4 and pgd1 showed both growth defects and suppression when combined with swi6, but a third tail component, gal11, showed neither. It has been suggested that GAL11 mutants prevent association of other tail module subunits (Lee et al 1999;Park et al 2000). If that were the case, we would expect the gal11 phenotypes to include all the phenotypes associated with loss of Sin4 and Pgd1.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the tail module components sin4 and pgd1 showed both growth defects and suppression when combined with swi6, but a third tail component, gal11, showed neither. It has been suggested that GAL11 mutants prevent association of other tail module subunits (Lee et al 1999;Park et al 2000). If that were the case, we would expect the gal11 phenotypes to include all the phenotypes associated with loss of Sin4 and Pgd1.…”
Section: Discussionmentioning
confidence: 99%
“…It is not yet clear whether truly species-specific MED subunits exist. Still, the emergence or exchange of additional metazoan-specific subunits, as well as mixing and matching among various modular subcomplexes such as those detected in yeast (Lee and Kim 1998;Lee et al 1999), may have been an important element contributing to the diversification of genetic programs in complex organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the formation of the preinitiation complex (PIC), transcription initiation, and the elongation and polyadenylation/termination stage each are associated with a distinct pattern of CTD phosphorylation. During the formation of PIC on the promoter DNA/chromatin template, transcription activators bind the coactivator protein complex, Mediator (Lee et al, 1999), which binds to the predominantly nonphosphorylated or hypophosphorylated form of Pol II and class II basal transcription factors (TFII). The TFIID component of PIC contains the TATA binding protein (TBP) that binds the TATA box sequence of promoters, as well as other TBP-associated factors (TAFs) or TBP-related factors involved in binding to promoters, particularly in those lacking a TATA box (MĂŒ ller et al, 2007;Juven-Gershon and Kadonaga, 2010).…”
Section: Introductionmentioning
confidence: 99%